2015
DOI: 10.1007/s00339-015-9489-1
|View full text |Cite
|
Sign up to set email alerts
|

Thermal conductivity reduction in graphene with silicon impurity

Abstract: We present a molecular dynamics investigation on the thermal conductivity of silicon-doped graphene and the resulting change in phonon properties. A significant reduction in the thermal conductivity is observed in the presence of silicon impurity even at a small concentration of silicon atoms. Conductivity values continued to decrease with an increase in silicon concentration. The increase in the scattering rate, which is measured by the reduction or broadening of the peaks of the van Hove singularities, is th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 56 publications
0
11
0
Order By: Relevance
“…Hence a technique to increase the Seebeck coefficient and simultaneously decrease the thermal conductivity is highly desired. Very recent studies [41,42] have shown that doping of and impurities in graphene sheets will decrease the ther-mal conductivity. Pop et al [43] have mentioned that any surplus residue from sample fabrication or any form of disorder will reduce the thermal conductivity further.…”
Section: A Electrical Conductivity and Seebeck Coefficient Of Mlgmentioning
confidence: 99%
“…Hence a technique to increase the Seebeck coefficient and simultaneously decrease the thermal conductivity is highly desired. Very recent studies [41,42] have shown that doping of and impurities in graphene sheets will decrease the ther-mal conductivity. Pop et al [43] have mentioned that any surplus residue from sample fabrication or any form of disorder will reduce the thermal conductivity further.…”
Section: A Electrical Conductivity and Seebeck Coefficient Of Mlgmentioning
confidence: 99%
“…28−30 Graphene is reported to be an excellent candidate for providing high-thermoelectric performance. 31,32 However, it is quite challenging while considering the thermal transport between the layers. Here, graphene plays a crucial role during the heat transfer and this makes it a unique candidate for thermoelectric applications.…”
Section: Introductionmentioning
confidence: 99%
“…The device lifetime and carrier mobility are thus reduced impacting the overall performance of the electronic devices with the increase in temperature. However, graphene-based transistors with the Joule heating effect have the ability to result in the upsurge of local-temperature hotspots at positions corresponding to the minimal carrier density in sync with the density of states. , The study of electronic transport, especially at graphene contacts, thus continues to garner significant interest as a prelude to the graphene nanoelectronics. The major issue with the nanoelectronic devices is the self-heating and this can be well quantified by using interfacial heat transfer and thermal transport at the nanoscale. Graphene is reported to be an excellent candidate for providing high-thermoelectric performance. , However, it is quite challenging while considering the thermal transport between the layers. Here, graphene plays a crucial role during the heat transfer and this makes it a unique candidate for thermoelectric applications.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly there are plans to use PnC structures to control thermal transport in quantum bits [18]. Previously this kind of control was achieved by introducing scattering centers, such as nanoparticles or impurities, into the material [19][20][21]. However, it has been shown that thermal transport can also be controlled with periodic PnC structures [22][23][24].…”
Section: Introductionmentioning
confidence: 99%